2006
DOI: 10.1080/02841850500445298
|View full text |Cite
|
Sign up to set email alerts
|

Standardized volume rendering for magnetic resonance angiography measurements in the abdominal aorta

Abstract: Purpose: To compare three methods for standardizing volume rendering technique (VRT) protocols by studying aortic diameter measurements in magnetic resonance angiography (MRA) datasets. Material and Methods: Datasets from 20 patients previously examined with gadolinium-enhanced MRA and with digital subtraction angiography (DSA) for abdominal aortic aneurysm were retrospectively evaluated by three independent readers. The MRA datasets were viewed using VRT with three different standardized transfer functions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The arrival of contrast material is controlled with real-time imaging (care bolus technique). In patients with GFR <30 ml/min×1.73 m 2 , time-of-flight and phase-contrast sequences can be used, even though image quality is lower and veins are also visualized [47].…”
Section: Mr Angiography (Mra)mentioning
confidence: 99%
See 1 more Smart Citation
“…The arrival of contrast material is controlled with real-time imaging (care bolus technique). In patients with GFR <30 ml/min×1.73 m 2 , time-of-flight and phase-contrast sequences can be used, even though image quality is lower and veins are also visualized [47].…”
Section: Mr Angiography (Mra)mentioning
confidence: 99%
“…L'acquisizione avviene in apnea, senza sincronizzazione elettrocardiografica, con controllo visuale dell'arrivo del MdC mediante imaging in tempo reale (tecnica care bolus). In caso di GFR <30 ml/min×1,73 m 2 è possibile impiegare sequenze angiografiche senza MdC (time of flight e phase contrast) ottenendo però immagini di qualità inferiore comprendenti anche i vasi venosi [47].…”
Section: Angio-rmunclassified
“…To overcome this problem, Lundstroem et al [16] utilize partial range histograms to improve tissue classification based on traditional one-dimensional (1D) TFs and add a second dimension to the TF that represents a classification certainty related the shape of specific tissue and its proximity to other tissues. A clinical study demonstrated sufficient accuracy of the approach based on partial range histograms for the assessment of abdominal aortic aneurysms in MR angiography datasets [17]. Lundström et al [18] focuses on 1D TFs but utilizes an alpha histogram that considers spatial coherence to propose useful TF settings.…”
Section: Related Workmentioning
confidence: 99%